The effect of adding sweet bean seed powder (Foeniculum vulgare) and Roselle (Hibiscus sabdariffa) seed powder on the growth performance of common carp Cyprinus carpio L. - Hasan Haydar (Mesopotamia Journal of Agriculture)
Seven experimental diets were prepared to feed the common carp Cyprinus carpio L.They are the control diet without additives T1 and three diets to which sweet bean seed powder was added in three proportions, namely 0.5%,1% and1.5%, respectively, for the diets T2, T3 and T4, and the diets contained T5 and T6. And T7 on Gujarat seed powder at rates of 0.5%, 1% and 1.5%, in an experiment that lasted for 60 days. The T5, T6, and T7 treatments, which contained Roselle seeds weighing (21.24, 24.07, 22.12) grams, respectively, were superior in weight gain to the control treatment T1 and T4 (18.06, 19.29) grams in weight gain of fish for all treatments compared with the control treatment and the rest of the treatments. Treatment T6 recorded a daily growth rate of 0.401 gm, superior to control treatment T1 (0.250 gm) and to the rest of the treatments. The specific growth rate increased signific in the Roselle seed powder treatments over the control treatment and the sweet bean seed powder treatments, where the T5 0.216 g/day treatment outperformed all treatments,including the control treatment. TheT2 treatment(0.168 g/day)outperformed the control treatment and the T3 and T4 treatments (0.143, 0.111)g/day. The relative growth rate increased significin treatments T5, T6, and T7 with percentages of (13.873, 11.035, and 11.053) %, respectively,over treatments T1,T3،T4,.Treatments T1 and T4 recorded (8.322 and 8.289) grams, respectively, superior to all the remaining treatments. The feed efficiency rate increased in treatment T6, amounting to 19.256%